The gravitational effects of blood flow in irregular stenosed artery with various severity / Yan BinTan and Norzieha Mustapha - Yan, Bin Tan; Mustapha, Norzieha (Unit Penerbitan UiTM Kelantan, 2016)
The mathematical study investigates the influences of gravitational force in an artery segment onthe various severity of the stenosis. Blood flow along the arterial segment is considered as incompressible Newtonian fluid. An unsteady two-dimensional nonlinear model is taken where the governing Navier-Stokes equations are added with significant gravity term. Marker and Cell (MAC) method based on finite difference approximations in a staggered grid is selected to solve the problem. Results obtained show that slight difference of areal occlusion percentage of severe stenosis in a vessel can lead to significant impacts on blood flow patterns. With the presence of the gravitational acceleration force, the pressure and axial velocity along the vessel is generally higher than without the gravitational force. Besides, the wall shear stress is lowerand therecirculation region is smallerin the presence of gravitational force